Diplomasi Indonesia di Laut Natuna Utara dalam Menghadapi Cina untuk Melindungi Kepentingan Nasional - Gerald Theodorus Lumban Toruan; Adi Sunaryo (Neolectura, 2020)
North Natuna Sea is become a concern, at the end of 2019 to February 2020 this area was illegally entered by Chinese fishing vessels who wanted to fishing, this vessel was escorted by the Chinese Coast Guard. This escort is in order to protect their fishing vessels from the pursuit of Indonesian patrol vessels. According to the them that they did not violate Indonesian territory, they said that the North Natuna Sea still belongs to Chinese territory. In the perspective of the international relations what is done by China can disrupt the stability of regional security. This research is a qualitative descriptive with secondary data collection. The formulation of the research question is what kind of diplomacy is being carried out by Indonesia towards China in the North Natuna Sea. The purpose of this research is to find the right diplomacy concept in dealing with the China in the North Natuna Sea.